Managing Failed Anti-Reflux Therapy - Ferguson, Mark K.; Fennerty, M. Brian; SpringerLink (Online service) (London : Springer London, 2006)
Gastroesophageal reflux disease (GERD) affects millions of people in western society. Since the introduction of laparoscopic techniques in the 1990s, it is now one of the most common indications for surgery. This multiauthored text provides information on the pathophysiology of GERD, appropriate medical management, and proper indications for and performance of surgical and endoscopic procedures for GERD. Thousands of patients will experience inadequate relief from medical therapy or will develop complications from their procedures or recurrent or new symptoms afterwards; this text describes in detail the proper evaluation and management of such patients. Beginning with an overview of the current understanding of the pathophysiology of GERD, the book moves onto new information regarding tissue susceptibility, the role of bile and digestive enzymes, and cyclic changes in LES tone. The next chapters are devoted to standard therapeutic options for GERD, including lifestyle changes, pharmacologic therapy, and surgery. In addition, newer endoscopic treatments, such as Stretta, Endocinch, injection of bulking agents, as well as others, are described. Subsequent chapters focus on the causes for failure of medical, endoscopic, and surgical therapies. The remainder of the text is a detailed examination of medical, endoscopic, and surgical remedies for these treatment failures. This text is essential to any physician who manages patients with GERD, including internists, gastroenterologists, general surgeons, and thoracic surgeons.
The Epidemiology and Pathophysiology of Gastroesophageal Reflux Disease -- History of Medical and Surgical Anti-Reflux Therapy -- Medical Management of GERD: Algorithms and Outcomes -- Complications of GERD: Esophagitis, Stricture, Barrett$1 (Bs, and Cancer -- Principles of Successful Surgical Anti-Reflux Procedures -- Acute Complications of Anti-Reflux Surgery -- Persistent Symptoms after Anti-Reflux Surgery and their Management -- Technical Surgical Failures: Presentation, Etiology and Evaluation -- Symptoms after Anti-Reflux Surgery: Everything Is Not always caused by Surgery -- The Medical and Endoscopic Management of Failed Surgical Anti-Reflux Procedures -- Reoperation for Failed Anti-Reflux Surgery -- Management of Alkaline Reflux -- Management of the Short Esophagus -- Esophagectomy: Indications, Techniques, and Outcomes -- Vagal Sparing Esophagectomy -- Future Directions of Therapy for GERD.s
Keywords: Medicine; Gastroenterology; Surgery; Thoracic surgery; Medicine & Public Health; Gastroenterology; General Surgery; Thoracic Surgery; Electronic books